Pendampingan Menulis Cerita Fabel Berbasis Kearifan Budaya Lamaholot di SMPS Ratu Damai, Flores Timur - Wissang, Imelda Oliva; Pande, Rikardus; Deta, Bernadete (LP2M INSURI Ponorogo, 2023)
Assistance in writing fairy tales for students at school is very important. Fairy tales are stories from the animal world that aim to entertain as well as a medium of moral education. Fable writing skills can only be achieved through directed, guided, and continuous practice in learning literature where students can translate their ideas, creative thoughts, and feelings into written language. This assistance aims to explain the implementation of the Lamaholot culture-based fable story writing activity with image media to the students of Ratu Damai class. The method used is the KKN method which directly assists students in writing fables using media images with implementation stages, including (1) the pre-implementation stage, (2) the analysis stage, (3) the training stage, (4) the mentoring stage, and (5) evaluation stage. This stage of activity is adjusted to the structure of the fable story which includes orientation, complication, resolution, and coda. Through fable writing assistance using image media, students can write fables which can be seen from the work in the form of fables written with imagination, high creativity, and interesting titles and moral messages conveyed regarding Lamaholot's cultural wisdom towards the marine environment. This guided activity can monitor students' interest and creativity in writing fables based on a given theme.